2022
DOI: 10.1111/jonm.13831
|View full text |Cite
|
Sign up to set email alerts
|

Work environment, resilience, burnout, intent to leave during COVID pandemic among nurse leaders: A cross‐sectional study

Abstract: Aims The aims of this work are to (1) investigate the work environment, resilience, burnout, and turnover intention and (2) examine how work environment and personal resilience impact burnout and turnover intention among nurse leaders in the midst of the COVID‐19 crisis. Background The COVID‐19 pandemic introduced tremendous stressors to nurse leaders, for example, managing the complex staffing situation while balancing patients' and family's needs. Methods During May to September 2021, an electronic survey wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
0
12
0
1
Order By: Relevance
“…This is consistent with other studies that found burnout was associated with or a common reason for manager turnover intention. 17,23,27 Nurses and nurse managers also experienced extraordinary stressors during the pandemic that may have impacted psychological health and well-being. Higher scores on the Secondary Traumatic Stress scale would indicate that the participant may need to discuss any work stress-related symptoms with a professional.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with other studies that found burnout was associated with or a common reason for manager turnover intention. 17,23,27 Nurses and nurse managers also experienced extraordinary stressors during the pandemic that may have impacted psychological health and well-being. Higher scores on the Secondary Traumatic Stress scale would indicate that the participant may need to discuss any work stress-related symptoms with a professional.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with other studies that found burnout was associated with or a common reason for manager turnover intention. 17,23,27…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] Nurses who are resilient are more likely to contribute to positive organizational and nursing care outcomes in addition to high work performance, high job satisfaction, high workforce sustainability, high patient care quality, high well-being, and low burnout. [2,3] By understanding nurses' resilience, it may be possible to enhance these positive effects. There has, however, not yet been published a comprehensive guide to Nurse resilience by means of bibliometric analysis.…”
Section: A Comprehensive Understanding Of Nurse Resilience Is Neededmentioning
confidence: 99%
“…There is evidence that resilience training, as well as its associated positive effects, is associated with a reduction in burnout risks among health workers. [2] Research literature [3] has demonstrated that resilience training reduces the risk of burnout among health workers who face workplace problems. The ability of a nurse to develop resilience not only facilitates their recovery but also serves as a motivational tool for their colleagues.…”
Section: Introductionmentioning
confidence: 99%